(untitled) (UNED Research Journal, 2019)
Introduction: The demography of the band tailed pigeon is not well known, because its habitat and habits make it difficult to locate them, observe them or catch an adequate sample of individuals. It is relevant to know the distribution, the types of habitat and the productivity of this species of pigeon, since any management measure must have information on these aspects. Objective: To characterize the vegetation of three observation sites of band tailed pigeons to generate information about their basic requirements and propose management measures. Methods: For the study of the composition and floristic structure the square-center point method was used, a total of 186 trees with a diameter at breast height (DBH) ≥10cm were measured. Results: In all three sites, about 50% of the individuals are grouped in the lower diameter classes and decreased in number in the larger diameter classes. The dense forest presented the highest number of species (N=17) followed by the agroforestry system (N=13) and with a smaller number the wooded paddock (N=4). The most abundant species were Myrsine coriacea in the wooded pasture, Rhamnus oreodendron in the agroforestry system and Freziera candicans in the dense forest. The composition of the vegetation of the three sites is not similar but species were found in common which coincides with other places of occurrence of the species in the country, these species could be determining the presence of band tailed pigeon. Conclusion: The implementation of agroforestry systems in coffee growing sites and the conservation of forest patches should be encouraged. I recommend the application of the methodology in other observation sites of band tailed pigeon in order to evaluate and compare the vegetation that is being used to establish important species and changes in vegetation cover.